Design of an Autonomous Effective Area Scanning Robot - Koroglu, Uygar; Islamoglu, Usame; Uslu, Erkan; Cakmak, Furkan; Altuntas, Nihal; Amasyali, M. Fatih; Yavuz, Sirma (IEEE, 2019)
Area scanning can be defined as complete coverage of an area delimited either by natural or virtual borders, by a mobile robot. Area scanning has a wide spread usage from home cleaning vacuum clear for home users to minesweeping robot for military usage. Autonomous mobile robot design and software implementation for effective area scanning of an initially unknown area is realized with this work. Simultaneous localization and mapping (SLAM), area segmantation, complete coverage path planning (CCPP) algorithms are used for this purpose. Behavioural approach is implemented at the top level by means of SMACH based state machine for autonomous effective area scanning. Calculated orientation of the environment and previously visited areas are used for effective path planning. Software implementation is tested on a differantial drive, Robot Operating System (ROS) capable mobile platform.
Keywords: ROS; robotics; autonomous; mobile robot; area scanning; behavioural approach; state machine; SMACH; simultaneous localization and mapping; SLAM; room segmentation; complete coverage path planning; CCPP; Computer Science